CLASSICAL TEST THEORY OF INNAPROPRIATE INDEX SCORE’S ACCURACY COMPARISON USING CONFUSION MATRIX ACCURACY PROPORTION IN EDUCATIONAL MEASUREMENT - Wardani Rahayu; Eko Wahyudi (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2017)
The objective of this study is to determine the Donlon Fischer aacuracy method, Jacob and SHL inappropriate score using confusion matrix accuracy proportion. This research was conducted by analyzing secondary data in response to the physics national examination results throughout the West Kalimantan Province in 2012 using 1545 research samples. The sampling of the research is done by using the random sampling technique of 1545 population. The research method is experimental method which is done by comparing the proportion of accuracy obtained from confusion matrix. The hypothesis was tested by using a differences in proportions Z test. Test results showed that the SHL inappropriate index score is more accurate than Donlon Fischer and Jacob innapropriate index score. This research is expected to find an accurate method in detecting the inappropriate score used as an evaluation parameter for educational measurement.